2008
DOI: 10.3758/pp.70.7.1248
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for criterion shifts in visual perceptual learning: Data and implications

Abstract: ) documents the range of tasks in which practice on elementary visual judgments can produce dramatic improvements in performance. This behavioral evidence has been used to motivate the development of a range of models for the mechanisms of perceptual learning (e.g., Adini & Sagi, 2001;Adini, Sagi, & Tsodyks, 2002;Gold, Bennett, & Sekuler, 1999;Gold, Sekuler, & Bennett, 2004;Petrov, Dosher, & Lu, 2005;Yu, Klein, & Levi, 2004), with the majority of these models focused on how perceptual sensitivity to either the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 102 publications
0
24
0
Order By: Relevance
“…Since the yes/no procedure that we have used is sensitive to response bias [37], the procedure may have had a significant impact on the reported thresholds. To check for this possibility, we have reanalyzed the data by calculating d ', which is a measure of sensitivity that is independent of bias.…”
Section: Resultsmentioning
confidence: 99%
“…Since the yes/no procedure that we have used is sensitive to response bias [37], the procedure may have had a significant impact on the reported thresholds. To check for this possibility, we have reanalyzed the data by calculating d ', which is a measure of sensitivity that is independent of bias.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that perceptual learning can induce significant changes in response bias, such as an increase in detection false alarms rates (Seitz, Nanez, Holloway, Koyama, & Watanabe, 2005; Wenger & Rasche, 2006; Wenger, Copeland, Bittner, & Thomas, 2008). Thus, we also calculated the response bias according to the SDT criterion, c .…”
Section: Resultsmentioning
confidence: 99%
“…The use of an illusory detection paradigm (i.e., only noise images) introduces a complication in that some observers may produce much higher false alarm rates than other observers (Wenger et al 2008). To the extent that this occurs, it introduces noise in the CIs because some observers respond due to a bias to respond in general rather than respond based on a good match between the noise image and their internal template.…”
Section: Discussionmentioning
confidence: 99%